STUDIES ON ENVTRONMENTAL ASSOCIATION CORRELATION IN HYBRID TEA ROSE (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
Rose is famous Ornamental and floriculture crop and its flower are demanded with handsome price. The production of flower is increasing which ensure the development of this industry. Investigation on present project dealing with flower yield component and genetic divergence in hybrid tea rose in 50 varieties of rose in randomenized block design with three replication were carried out at C.S. Azad University ofof agriculture and technology during 1998-99 and 1999-2000.